Proteínas do plasma seminal de touros Bos Indicus e associações com parâmetros seminais - Silva, Michelle Moura da (2011)
This research aimed to describe the two-dimensional electrophoresis map of bull seminal plasma of adult Bos indicus, Brahman, and the determination of statistical associations between proteins of seminal plasma and semen parameters of these bulls. Semen samples from 56 bulls were collected and seminal plasma was obtained by centrifugation and subjected to two-dimensional electrophoresis. The gels were stained with colloidal Coomassie, scanned and analyzed using PDQuest application. The bulls were divided into groups of high and low sperm motility and high and low percentage of morphologically normal sperm cells. The most abundant proteins in seminal plasma of bulls Bos indicus and detected in all 56 gels showed similarity to espermadesinas and BSPs. The expression of spots with pI values ​​kDa protein equivalent to aSFP, BSPs, clusterin, albumin and osteopontin were significantly different between groups of animals with contrasting parameters of sperm motility and morphology. The associations found between such protein spots and semen parameters suggest the possibility of their use as molecular markers of potential fertility of animals.